2016
DOI: 10.1002/ange.201510825
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst‐Controlled Switch in Chemo‐ and Diastereoselectivities: Annulations of Morita–Baylis–Hillman Carbonates from Isatins

Abstract: Regulating both the chemo‐ and diastereoselectivity, divergently, of a reaction is highly attractive but extremely challenging. Presented herein is a catalyst‐controlled switch in the chemo‐ and diastereodivergent annulation reactions of Morita–Baylis–Hillman carbonates, derived from isatins and 2‐alkylidene‐1H‐indene‐1,3(2H)‐diones, in exclusive α‐regioselectivity. α‐Isocupreine efficiently catalyzed [2+1] reactions to access cyclopropane derivatives, and the diastereodivergent [3+2] annulations were accompli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…[7] As aresult, it would be highly challenging to chemoselectively combine Lewis base activated intermediates of MBH derivatives with active p-allylpalladium species generated from other allyl derivatives.I nf act, there is no successful report dealing with cooperative catalysis for MBH derivatives under organo and metal catalysis to date. [8] With our continuing interest in developing new transformations of MBH derivatives, [9] here we disclose that highly chemoselective activations of MBH carbonates,from isatins,and allylic carbonates can be accomplished by atertiary phosphine/Pd 0 complex for the first time (Scheme 1c). Thus, g-regioselective allylicallylic alkylation between IV and V occurred accordingly.…”
mentioning
confidence: 91%
“…[7] As aresult, it would be highly challenging to chemoselectively combine Lewis base activated intermediates of MBH derivatives with active p-allylpalladium species generated from other allyl derivatives.I nf act, there is no successful report dealing with cooperative catalysis for MBH derivatives under organo and metal catalysis to date. [8] With our continuing interest in developing new transformations of MBH derivatives, [9] here we disclose that highly chemoselective activations of MBH carbonates,from isatins,and allylic carbonates can be accomplished by atertiary phosphine/Pd 0 complex for the first time (Scheme 1c). Thus, g-regioselective allylicallylic alkylation between IV and V occurred accordingly.…”
mentioning
confidence: 91%
“…This is surprising, because as early as in 1999, Carreira et al 34 – 37 have successfully utilized unprotected or N -benzyl spirocyclopropyl oxindoles to build up the spiro[pyrrolidine-3,3′-oxindole] ring systems via MgI 2 -catalyzed annulation with imines. Since the absolute configuration and the substituent of the C3 spiro stereocenters of spirocyclic oxindoles greatly influenced the biological activities 38 , 39 , it is of current interest to exploit new catalytic enantioselective methods for the synthesis of spirocyclic oxindoles that are prominent structural motifs in natural products and drugs 38 53 . While enantioselective cycloaddition using spirocyclopropyl oxindoles as D–A cyclopropanes constitutes a new entry for diverse synthesis of optically active spirocyclic oxindoles, it is difficult to make use of such monoactivated D–A cyclopropanes, for two reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Chen's group reported the asymmetric cycloaddition reactions of isatin‐derived MBH carbonates 164 with 2‐alkylidene‐1 H ‐indene‐1,3(2 H )‐diones 161 , catalyzed by various chiral Lewis bases, leading to a switch in chemo‐ and diastereoselectivity. [ 57 ] They demonstrated that the highly enantioselective [3+2] reactions could be achieved in the catalysis of chiral tertiary phosphine 128 to afford product 168 , and the diastereoselectivity could be switched by using another chiral phosphine catalyst 169 or chiral amine catalyst to give product 170 (Scheme 38). All reactions exhibited exclusive α‐regioselectivity and good to outstanding stereoselectivity, thus furnishing a collection of complex compounds having structural and stereogenic diversity.…”
Section: Cycloaddition Reactions Catalyzed By Chiral Phosphinesmentioning
confidence: 99%